2002
DOI: 10.1136/bjo.86.11.1278
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing visual outcome in anisometropic amblyopes

Abstract: Aim: To identify which factors influence the final visual acuity in children with anisometropic amblyopia. Methods: A retrospective analysis of 112 children with anisometropic amblyopia, identified from examining all case notes of children who had failed preschool or school screening. Results: The age at presentation had no effect on the final visual outcome (p=0.804). Both the degree of refractive error and the degree of anisometropia at presentation correlated with final visual acuity (p<0.001 and p=0.001). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 15 publications
(8 reference statements)
3
36
2
4
Order By: Relevance
“…Our data demonstrated that age had no significant impact on the success of treatment. fluence of smaller refractive errors on treatment success, while Hussein et al, demonstrated no effect of the amount of difference in refraction between both eyes on treatment success [8,14,15]. Our data differs from several other studies with regards to the effect of compliance and presenting visual acuity on treatment success.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Our data demonstrated that age had no significant impact on the success of treatment. fluence of smaller refractive errors on treatment success, while Hussein et al, demonstrated no effect of the amount of difference in refraction between both eyes on treatment success [8,14,15]. Our data differs from several other studies with regards to the effect of compliance and presenting visual acuity on treatment success.…”
Section: Discussioncontrasting
confidence: 93%
“…Hussein et al, demonstrated an increased risk of treatment failure if treatment was started after the age of 6 years old [8]. However, Cobb et al, and Chen et al, found no correlation between age and treatment success [13,14]. Our data demonstrated that age had no significant impact on the success of treatment.…”
Section: Discussioncontrasting
confidence: 41%
“…There are published studies that report the effectiveness of treatment is no different if commenced any time between 3 and 7 years of age [7][8][9] and that deferring treatment until the age of 5 years does not appear to limit potential for improvement. 10 There are also suggestions in the literature that the window for treating amblyopia may be wider than current practice would suggest; 11,12 some even suggest a response to treatment at up to 17 years of age, though recognise compliance may become more difficult with increasing age.…”
Section: Introductionmentioning
confidence: 99%
“…17,[36][37][38] Most literature suggests that anisometropia leads to amblyopia, 16,30,32,[37][38][39] but some provide evidence that amblyopia may be the primary cause. 36 Either way, the onset of anisometropia and the onset of amblyopia are likely to occur at different ages.…”
Section: Onset Of Anisometropia Versus Onset Of Amblyopiamentioning
confidence: 99%
“…The majority agree that a minimum interocular difference of 1 dioptre (D) is required to define anisometropia, [1][2][3][4][5][6][7][8][9][10][11] but the definition varies between 0.5D [12][13][14] and 2D. 15,16 The overall prevalence of anisometropia ranges from less than 1% to 1.6%. 11,17 It is a significant problem if left untreated as it can be associated with amblyopia in the more ametropic eye.…”
Section: Introductionmentioning
confidence: 99%